DIGITAL MARKETING PERSPEKTIF ETIKA BISNIS ISLAM: A DIGITAL MARKETING PERSPECTIVE OF ISLAMIC BUSINESS ETHICS - Ismatul Khayati (JOURNAL KOPERASI DAN MANAJEMEN, 2022)
Purpose – The purpose of this study is to analyze digital marketing carried out by celebrities on Instagram social media based on the perspective of Islamic business ethics. Design/methodology/approach – This research method is qualitative with a case study approach and data analysis as qualitative descriptive. Findings – The study results show that digital marketing activities on Instagram do not fully comply with Islamic business ethics principles, especially Unity, Responsibility, and Honesty. Meanwhile, the principle of Equilibrium and the principle of Free Will can be said to have been sufficiently implemented. Research limitations/implications – This case only discusses business actors who, together with Celebgram, have not fully complied with unity, responsibility, and honesty. And have not discussed it from another point of view. Originality/value – Entrepreneurs on social media Instagram services, reviewed in light of the principles of Islamic business ethics, show that digital marketing has not fully complied with the principles of Islamic business ethics. Keyword : Digital Marketing, Instagram, Islamic Business Ethics Paper type: Case Study